(untitled) (Impact: Journal of Transformation, 2022)
Research has shown that the trend of teenagers engaging in drug and substance abuse is on the rise. In spite of the increase of male adolescents abusing drugs, a situation that escalated during the Covid-19 break, it is perplexing that some boys have been resilient to overcome the challenge, though exposed to the same risk factors as those who abuse drugs and substances. Therefore, using an interpretive framework, the aim of this research was to document the lived experience of these teenage boys who have managed to avoid engaging in drug and substance abuse. The main research question was: How have male teenagers in Kabete High School in Kiambu County overcome the challenge of drug and substance abuse despite their vulnerability? The research adapted the Problem-Behavior theory of Jessor and Jessor in line with variables in the thematic framework. A public boys’ high school was selected for this study. The sampled population comprised 5 male teenagers who were purposely selected for the interview. Further, a focus group discussion of 6 students was carried out and the deputy principal was interviewed. The methodology used was a qualitative case study which was anchored on lived experiences; observation guides and field notes were used to collect data. Emerging themes that were identified are: Challenging home environment, parental control, positive self-concept of the participants, avoidance of negative peer influence, and faith in God. These themes have been discussed in the paper and recommendations given.